En Ardèche, les causes de feux varient entre cantons voisins - Alexandrian D. (Les incendies de forêt en région méditerranéenne : constitution et utilisation des bases de données, 1995)
A departemental scheme was developed to define high risk areas for forest fire. Certain cantons in the Ardèche (France) were examined more specifically. Three examples are used to show the value of the definition of causes of fires. This paper describes the methodology and gives some results. In conclusion, it can be said that the causes of forest fires vary strongly in region that at first sight appear to be homogeneous. Cross-checking several sources of information and especially examination of statistics make it possible to gain a fairly objective picture of the problem in the area.
Séminaire sur les Incendies de Forêt en Région Méditerranéenne, 1993/11/30-1993/12/04, Montpellier (France)